Die Haftung des Staates für legislatives Unrecht in Deutschland und Japan - Olberg, Susanne (Zeitschrift für Japanisches Recht, 2009)
The procedural options to achieve the constitutional review of a law are limited in Japan. The Japanese legal practice tries to compensate for the lack of a petition based on allegation of infringement of the constitution by other methods. These include inter alia an action for damages against the Japanese state because of a legislative wrong, which incidentally achieves the constitutional review of a law. Legislative wrong includes the enactment of an unconstitutional law as well as the unconstitutional failure to enact a certain law. Neither Japanese state liability law nor German law expressly regulates state liability for legislative wrong. At first glance, state liability for legislative wrong would seem to be self-evident in a constitutional state. On the other hand, state liability for legislative wrong might lead to a high financial burden on the state finances, which in turn could indirectly limit the scope of the legislator. The article compares how this question is dealt with in German and Japanese law. In the first part, the article displays the German state liability rules and their interpretation by the courts and legal literature. The prerequisite for German state liability requires the violation of an official duty to a third party by an officer. Therefore, the question revolves around whether the members of Parliament are obliged to the citizens when they participate in legislating. In the second part, the article depicts the Japanese controversy and analyzes the relevant judgements of the Japanese Supreme Court. The Supreme Court makes a distinction between the unconstitutionality of a law and the unlawfulness of a legislative act in the sense of state liability law. The main point of the Japanese controversy is therefore the question under which preconditions a legislative wrong is unlawful. Despite the different wording of the relevant laws, the Japanese Supreme Court and the German Federal Court of Justice adhere to similar interpretations that reduce state liability for legislative wrong to exceptional cases.